Spatiotemporal patterns of rheumatic heart disease burden attributable to high systolic blood pressure, high sodium diet, and lead exposure (1990 to 2019): a longitudinal observational study - Zhang, Yanli; Zhang, Jun; Liu, Yonggang; Zhou, Yuzhe; Ye, Lu; Chen, Kaiming; Jiao, Jinghua (Frontiers in Nutrition, 2024)
Background: Rheumatic heart disease (RHD) continues to be a significant global health concern, exhibiting unique regional disparities. Although there's a noted decline in the burden of RHD, the specific causatives for this decrease remain unclear. This study aims to identify and quantify the spatiotemporal patterns related to the RHD-attributable risk burden. Methods: Data pertaining to deaths and disability-adjusted life years (DALYs) attributable to RHD risk were drawn from the Global Burden of Disease (GBD) Study conducted from 1990 to 2019. These data, categorized by age, gender, and geographical location, highlighted risk factors including diets high in sodium, elevated systolic blood pressure, and lead exposure. To examine the long-term trends in RHD changes due to these specific risk factors, the average annual percentage change (AAPC) method was employed. Results: During the past 30 years, the highest decrease in RHD burden was attributed to high systolic blood pressure. An AAPC of -2.73 (95% confidence interval [CI]: -2.82 to -2.65) and -2.45 (95% CI: -2.55 to -2.36) in deaths and DALYs was attributable to high systolic blood pressure, while an AAPC of -3.99 (95% CI: -4.14 to -3.85) and -3.74 (95% CI: -3.89 to -3.6) in deaths and DALYs was attributed to diet high in sodium. Moreover, the trends in deaths and DALYs due to lead exposure also showed decreases with an AAPC of -2.94 (95% CI: -3 to -2.89) and -3.46 (95% CI: -3.58 to -3.34) from 1990 to 2019. Oceania showed an upward trend of the RHD DALYs due to high systolic blood pressure with AAPC to be 0.23 (95% CI: 0.13 to 0.33). In general, countries in Oceania, East Asia, and South Asia had higher age-standard deaths and DALYs rates of RHD due to diet high in sodium. Conclusions: Our study has revealed that high systolic blood pressure remains the prime risk factor contributing to the RHD burden. There is decreasing spatiotemporal patterns in RHDrelated deaths and burden. Gaining this knowledge is fundamental to making informed public health strategies and clinical decisions, especially concerning risk assessment, screening, and prevention initiatives.